1974
DOI: 10.1038/bjc.1974.96
|View full text |Cite
|
Sign up to set email alerts
|

Glycosidases in Normal and Dimethylhydrazine-Treated Rats and Mice with Special Reference to the Colonic Tumours

Abstract: Summary.-Activities of 12 glycosidases and of P-D-glucuronidase were measured in liver, kidney and in the gastrointestinal tract of rats and mice. The activities of different enzymes varied not only within one tissue but also among different tissues. In rats injected with 1,2 -dimethylhydrazine, a many fold increase indase and a-L-fucosidase was fountl in colonic tumours and colonic mucosa. These enzymes were elevated significantly in the kidney of tumour bearing animals as well. Liver and other parts of the g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

1974
1974
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…Human colon and breast carcinoma tissue have been reported to have elevated levels of some lysosomal glycosidases and protease activities as compared with normal adjacent tissue (64). In animals with carcinogen induced colon tumors there were increased levels in tumor associated [3-N-acetylglucosaminidase activity (65). In another study (66) the activities of [3-hexosaminidase A and B were measured in human lung carcinoma and adjacent normal tissue.…”
Section: A Changes In Cell Surface Glycoconjugates In Differentiatiomentioning
confidence: 96%
“…Human colon and breast carcinoma tissue have been reported to have elevated levels of some lysosomal glycosidases and protease activities as compared with normal adjacent tissue (64). In animals with carcinogen induced colon tumors there were increased levels in tumor associated [3-N-acetylglucosaminidase activity (65). In another study (66) the activities of [3-hexosaminidase A and B were measured in human lung carcinoma and adjacent normal tissue.…”
Section: A Changes In Cell Surface Glycoconjugates In Differentiatiomentioning
confidence: 96%
“…A number of investigators have reported the increased activity of this enzyme in association with malignant transformation (Bosmann and Hall 1974: Mian and Cowen 1974: Whitehurst et al 1982) and the enhanced metastasic ability of tumors (Varani et On the other hand, no significant difference in this enzyme level was observed in renal and colonic carcinoma (Kim and Isaacs 1975 ;Brattain et al 1977;Okochi et al 1979 ;Tsao et al 1979) and the decrease in its specific activity was reported in fast growing hepatoma and chronic lymphocytic leukemia (Weber et al 1973 ;Dempse et al 1980).…”
Section: Discussionmentioning
confidence: 99%
“…The remaining colons of the tumour bearing animals and the control colons were cut into 8 equal segments. (Mian and Cowen, 1974).…”
Section: Methodsmentioning
confidence: 99%
“…The descending colon, which after the DMH treatment showed a significant increase in the levels of glycosidases, also gave rise to a larger number of adenocarcinomata than other parts of the colon. The relative changes in the activities of four glycosidases seemed to show a good correlation.IN GENERAL, rat colonic tumours induced bv 1,2-dimethylhydrazine (DM1H) indicated a significant increase in the levels of some glycosidases compared with the remaining colonic mucosa of the treated animals (Mian and Cowen, 1974). Evidence of a generalized change, as indicated by an overall reduction of 35S uptake, in parts of the DMH treated rat colon where tumours were commonly developed has been given (Springer, Springer and Oehlert, 1970).…”
mentioning
confidence: 99%
See 1 more Smart Citation